Hyperbolic value addition and general models of animal choice - Mazur, James E. (Psychological Review, 2001)
Three mathematical models of choice-the contextual-choice model (R. Grace, 1994), delay-reduction theory (N. Squires & E. Fantino, 1971). and a new model called the hyperbolic value-added model-were compared in their ability to predict the results from a wide variety of experiments with animal subjects. When supplied with 2 or 3 free parameters, all 3 models made fairly accurate predictions for a large set of experiments that used concurrent-chain procedures. One advantage of the hyperbolic value-added model is that it is derived from a simpler model that makes accurate predictions for many experiments using discrete-trial adjusting-delay procedures. Some results favor the hyperbolic value-added model and delay-reduction theory over the contextual-choice model, but more data are needed from choice situations For which the models make distinctly different predictions.
Keywords: *Behavior, Animal; *Choice Behavior; *Models, Psychological; Animals; Behavior, Animal; Choice Behavior; Columbidae; Conditioning (Psychology); Conditioning, Psychological; Models, Psychological; Reinforcement (Psychology); Reinforcement Schedule; Reinforcement, Psychology; animal; animal behavior; comparative study; conditioning; decision making; dept.psy; pigeons and doves; psychological model; reinforcement; review; ⚠️ Invalid DOI